2013
DOI: 10.4269/ajtmh.2012.12-0048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Field-Portable DNA Microarray Platform and Nucleic Acid Amplification Strategies for the Detection of Arboviruses, Arthropods, and Bloodmeals

Abstract: Abstract. Highly multiplexed assays, such as microarrays, can benefit arbovirus surveillance by allowing researchers to screen for hundreds of targets at once. We evaluated amplification strategies and the practicality of a portable DNA microarray platform to analyze virus-infected mosquitoes. The prototype microarray design used here targeted the nonstructural protein 5, ribosomal RNA, and cytochrome b genes for the detection of flaviviruses, mosquitoes, and bloodmeals, respectively. We identified 13 of 14 fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Subsequent detection is done by either agarose gel electrophoresis (followed by ethidium bromide staining) or hybridization with molecular probes (Houng et al, 2001; Scaramozzino et al, 2001; de Morais Bronzoni et al, 2005; Chao et al, 2007; Naze et al, 2009; Yeh et al, 2010; Grubaugh et al, 2013a; Grubaugh et al, 2013b). …”
Section: Introductionmentioning
confidence: 99%
“…Subsequent detection is done by either agarose gel electrophoresis (followed by ethidium bromide staining) or hybridization with molecular probes (Houng et al, 2001; Scaramozzino et al, 2001; de Morais Bronzoni et al, 2005; Chao et al, 2007; Naze et al, 2009; Yeh et al, 2010; Grubaugh et al, 2013a; Grubaugh et al, 2013b). …”
Section: Introductionmentioning
confidence: 99%
“…Probes were designed to target unique viral sequences, 30 to 45 nucleotides in length, between the GSPs using methods previously described [30]. A total of 2,097 oligonucleotide probes were selected for inclusion on the ArboChip5.1.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the assays included an unbiased, random amplification method for microarray detection. We have previously reported that such techniques are efficient for the amplification viral nucleic acids isolated from cultured cells, but not from a complex matrix of RNA from mosquito homogenates [30]. Additionally, most of the microarray designs are not wide-ranging and only cover a few of the most concerning viral pathogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a large number of recently launched portable devices that allow testing of forensic samples outside the laboratory. Many of these systems are based on familiar laboratory platforms, either utilising capillary electrophoresis (CE) based detection [22], microarray [23] or utilise melt curve detection of PCR amplicons [24,25].…”
Section: Introductionmentioning
confidence: 99%